Knowledge-Based Growth in Natural Resource Intensive Economies Mining, Knowledge Development and Innovation in Norway 1860-1940 - Ranestad, Kristin (Palgrave Studies in Economic History, 2018)
This book rejects the idea that natural resource industries are doomed to slow growth. Rather, it examines the case of Norway to demonstrate that such industries can prove highly innovative and dynamic. Here, the case is compellingly made that a key empirical problem with the popular 'resource curse' argument is that some of the richest countries in the world - namely Norway, Sweden, Canada and Australia - have all developed fast-growing economies based on natural resources. Analysis of innovation and knowledge development in natural resource industries reveal important new insights about the role of learning and innovation. These insights are key to understanding variances in growth levels between natural resource-based economies. Ranestad illustrates how Norway's high economic performance is built on knowledge-based natural resource industries. While Norwegian industries may have originated because of foreign technology and expertise, they thrived due to further developments carried out by organisations within Norway. Ranestad looks at how these developments were possible due to the country's high level of human capital, capacity for knowledge absorption and ability to adapt to new global technological and economic circumstances. Kristin Ranestad is a Postdoctoral Fellow at the University of Oslo, Norway. Her research interests are in economic history, global history and the history of technology.